Membatasi k-Ketenggaan Simpul dalam Pembangkitan Random Graph Metode Erdos Royi untuk Meningkatkan Kinerja Komputasi - Abidin, Zainal; Arifin, Agus Zainal (CAUCHY, 2010)
Edges generation by random graph erdos-royi methods was needed high computation, it’s caused low performance. In fact, edge generation was used frequently with many nodes. this paper is described a node restriction by k-nearest neighbour on edge generation of random graph erdos royi method. Result of noderestriction by k-nearest neighbour can be reduced computation time.